A year of online classes amid COVID-19 pandemic at a Bangladeshi university: Economics students’ experience and suggestions for improvements (Journal of Applied Learning and Teaching, 2021)
Current works perusing online learning amid the COVID-19 pandemic have several drawbacks, i.e., non-representative sample, closed-ended questions, and ignoring students’ opinions about improvement. Also, most studies were carried out in the first weeks of online classes, and no study focused on university-level economics students. This paper uses a convenience sampling technique and open-ended questions and collects data from 154 university-level economics students who have participated in online learning for a year. According to the findings, advantages of online classes include that students can do classes from home avoiding health risks, easy accessibility, flexibility, cost-saving, reducing the likelihood of semester loss, and learning new technologies. Major disadvantages are network problems, difficulties in understanding the topic, unsuitability for mathematical courses, concentration problems, non-interactive classes, financial constraints, adverse health impacts, device and internet problems. Disadvantages outnumbered advantages. Students made several suggestions: using state-of-the-art digital tools, recording and uploading lectures, resolving internet and network issues, holding classes that comply with a fixed schedule, greater efforts to make the topics easier, reducing class duration, institutional support, and introducing an online assessment system. The study makes several policy suggestions and reveals that 70% of problems can be resolved by the Department, the University, and the University Grants Commission.